Epidemiology of Trypanosoma evansi infection in horses in Peninsular Malaysia and the variant surface glycoprotein of the isolates - Elshafie, Elshafie Ibrahim (2011)
There is no current data regarding the epidemiology of Trypanosoma evansi infection in horses in Peninsular Malaysia. Previous publications on T. evansi were on reports of the disease. Therefore, a series of complementary studies were carried out on the epidemiology of T. evansi in horses. A cross-sectional study was conducted in eight states of Peninsular Malaysia to determine the prevalence of T. evansi in horses. A total of 527 blood samples was obtained and examined by Haematocrit Centrifugation Technique (HCT), Giemsa-stained thin blood smears (GSS) and Polymerase Chain Reactions (PCR). The results showed an overall parasitological prevalence of 0.57% (3/527, CI: 1.6-0.19%) with both HCT and GSS. Morphometric study revealed the mean total length of the trypanosomes including the free flagellum was 27.94 ± 2.63 μm. PCR successfully amplified a trypanosome specific 257 bp in 1.14% of samples (6/527, CI: 2.4-0.52%) and was confirmed by nucleotide sequences. The mean packed cell volume (PCV) for the positive cases detected by HCT was lower (23% ± 7.00) compared to the cases detected by PCR alone in Terengganu (35% ± 4.73). The overall seroprevalence detected by Card Agglutination Test for Trypanosoma evansi (CATT/T. evansi) was 13.90% (73/527, CI: 11.2-17.1%). A questionnaire was designed to collect data on risk factors associated with T. evansi seroprevalence. Two risk factors inferred by binary logistic regression were horse breed and gender (p < 0.05). The mean PCV value between the seropositive and seronegative groups was not significant (p > 0.05). The majority of the horse owners were not familiar with surra (85.30%). However, most of them were understandably very cautious with the health of their animals. It is generally assumed that local ponies are resistant to the disease caused by T. evansi. To test this assumption, an experimental study was carried out to assess the dynamics of T. evansi infection in Malaysian local ponies. Four local female ponies aged between three to seven years old were injected with a local T. evansi isolate, while another two ponies served as negative control. Parasitaemia was first detected on the 4th day post infection. The main clinical findings in the infected animals were fever, weight loss, successive weakness, reduction of appetite and finally led to death of one pony out of the four infected. Haematological changes in the infected group showed a significant decline in the mean total erythrocyte counts, PCV, haemoglobin, thrombocytes and neutrophils, whereas there was an increase in monocytes (p < 0.05). Biochemical parameters showed a significant elevation in indirect bilirubin, creatinine, urea and globulin values, while glucose, albumin, albumin/globulin ratio, aspartate aminotransferase and creatine kinase declined among the infected horses (p < 0.05). These haematological and biochemical changes were similar to previous reports of T. evansi infections in various hosts. The high morbidity and mortality observed in this study proves that Malaysian local ponies are susceptible to T. evansi infection. The T. evansi variant surface glycoproteins (VSG) repertoire and its dynamics of expression in the infected local ponies were assessed. Variant surface glycoprotein obtained from parasitaemia peaks of T. evansi were analyzed by amino acid sequences. T. evansi isolates from each pony expressed four or five distinctive VSGs throughout the infection period of 30 days. The primary structure of the VSGs indicated a hypervariable region in all VSG N-terminal domains, whereas C-terminal domains were relatively conserved. Certain VSGs were expressed by individual animals either at the same time or in the neighbouring parasitaemia peaks. The VSG N-terminal domain is responsible for the characteristic waves of parasitaemia in T. evansi infection and four to five VSGs are expressed by individual ponies in the early stage of the infection. In conclusion, this study showed T. evansi infection occurred in low frequency in horses in Peninsular Malaysia, and PCR is considered as a sensitive diagnostic tool. The good management systems adopted by horse owners are probably responsible for the low T. evansi occurrences. The disease seropositivity is associated with gender and breed of the horse. Local ponies are highly susceptible to T. evansi infection which is contrary to previous assumptions and the treatment regime applied was effective to rescue the remaining surviving animals.